Transformation of dissolved organic matter at a full-scale petrochemical wastewater treatment plant. (1st March 2023) - Kou, Yue; Jiang, Juntao; Yang, Baiyu; Sun, He; Wang, Leqi; Wang, Qinghong; El-Din, Mohamed Gamal; Shi, Quan; Chen, Chunmao
Abstract: Transformation of dissolved organic matter (DOM) in petrochemical wastewater (PCW) treatment has rarely been studied. In this work, low- and high-salinity PCW were collected from a treatment plant and the transformations of DOM at molecular level along the treatment processes of both PCW were comparatively investigated. By using Orbitrap MS, the polar DOM constituents were categorized into five molecular classes namely saturated compounds, aliphatics, highly unsaturated and phenolic compounds (Huph), polyphenols and condensed polycyclic aromatics (Cpla). Aliphatics (58.62%) with low molecular weight (150–250 Da) and O/C (0–0.2) were dominant in raw low-salinity PCW; while Huph (65.03%) with O/C at 0.2–0.8 were rich in raw high-salinity PCW. After full-scale treatment, differentiated DOM constituents in both raw PCWs were transformed into aliphatics and Huph with O/C at 0.3–0.5. Anoxic/Oxic treatment of low-salinity system (L-A/O) removed a high fraction of aliphatics (53.05%); while Huph with low O/C (0.1–0.3) (65.68%) in the effluent of L-A/O were further mineralized by ozonation of low-salinity system (L-ozonation). In comparison, anoxic/oxic treatment of high-salinity system (H-A/O) mainly removed unsaturated Huph (34.10%) and aliphatics (30.86%). This resulted in a decrease of dissolved organic carbon as indicated via Spearman correlation. Different from L-ozonation, ozonation of high-salinity system (H-ozonation) degraded aliphatics (26.09%) and Huph (41.85%) with a relatively high O/C (0.2–1.2). After L-A/O and L-ozonation treatments, remaining saturated compounds that were originated from raw low-salinity PCW, were removed by subsequent biological aerated filter. Comparatively, after H-A/O and H-ozonation treatments, residual Huph and aliphatics which were mainly bio-derivates and ozonated intermediates, were further removed by air flotation filter. Hence, DOM transformation of different PCWs along similar treatments varied significantly. This study provides in-depth insights on DOM transformation along a full-scale PCW treatment process. Graphical abstract: Image 1 Highlights: DOM transformation of PCW along L-system and H-system were comparatively investigated. L-system transformed DOM from Aliph, Huph and Plph to Aliph and Huph with higher O/C. Aliph and Huph kept as major DOM compositions while O/C decreased along H-system. L-A/O removed Satu and Aliph while H-A/O removed Huph and Plph. L-ozonation increased O/C of DOM while H-ozonation reduced O/C of DOM.